Neutrino oscillation effects in Soudan 2 upward-stopping muons - Allison, W; Alner, G; Ayres, D; Barr, G; Barrett, W; Border, P; Cobb, J; Cockerill, D; Courant, H; Demuth, D; Fields, T; Gallagher, H; et al. (2005)
Upward-going stopping muons initiated by atmospheric νμ and ν̄μ interactions in the rock below the Soudan 2 detector have been isolated, together with a companion sample of neutrino-induced single muons, created within the detector, which travel downwards and exit. The downward-going sample is consistent with the atmospheric-neutrino flux prediction, but the upward-going sample exhibits a sizable depletion. Both are consistent with previously reported Soudan 2 neutrino-oscillation results. Inclusion of the two samples in an all-event likelihood analysis, using recent 3D-atmospheric- neutrino-flux calculations, reduces both the allowed oscillation parameter region and the probability of the no-oscillation hypothesis. © 2005 The American Physical Society.